An Analysis of Pauses in Conversations By Students of The Faculty of Letters and Languages, Universitas Kristen Indonesia - Christyanto Fernandez Mulyohartono; YulesOrlandoSianipar (Prodi Sastra Inggris UKI, 2022)
This article discusses about pauses phenomenon and the factors that cause pauses among students of the Faculty of Letters and Languages, Universitas Kristen Indonesia. This article was made by using qualitative research methods and using the theory of Reed and Kahar. Data is taken from recorded transcripts of online classes. Then, the data regarding the pauses phenomenon will be classified according to the types of pauses based on Reed and Kahar's theory. After that, the factors or causes of the pauses phenomenon will be analyzed. The results showed that there were 51 data on pauses (41 data filled pauses and 10 data unfilled pauses), which means that there are many students of the Faculty of Letters and Languages, Universitas Kristen Indonesia who do the pauses for various reasons, ranging from nervousness, hesitation, and etc. In conclusion, the students from the Faculty of Letters and Languages, Universitas Kristen Indonesia use filled pauses more than unfilled pauses for reasons of nervousness and hesitation when they are talking. It is suggested that the students have to read more and practice speaking English regularly, increase English vocabulary, and the lecturers can also motivate students to practice so that they can minimize their pauses.